Menelusuri Fundamentalisme Sebagai Identitas Gerakan Keagamaan di Indonesia - Agus Muhaimin (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2018)
This article examines the emergence of fundamentalism as a political movement in the circle of world religions with their own backgrounds. The writer emphasizes on Islamic fundamentalism upholding the issues regarding Western colonialization so long as the first half of 20th century and economic and cultural neo-colonialism in the last half of the century. By literary study the writer concludes that these religious movements radically take religious doctrines as the fundamentals of the movement ideology. This movement is assigned with the slogan of ‘Islam as the alternative’ aiming at changing socio-political order towards Islamic norms through radical movements.